Penelitian mutu kulit sarung tangan golf samak krom - Sri Untari (Majalah Kulit, Karet, dan Plastik, 1992)
The Study aimed at improving the quality of chrome-tanned leather for golf floves producted by Indonesian tanners. Samples used in this study were 32. They were visually inspected and tested on their chemical and physical properties. The results of the chemical and physical tests were analyzed using deviation standard in descriptive statistics. It was obtained from the visual inspection of the samples taken that the leather was soft enough, the colour was even, their hair was not loose, and it was flexible but not elastic. While from the Chemical Tests, the results obtained were : water content (13,78 – 16,94) %; Fat Content (6,04 – 11,38) % and pH Valueness (4,43 – 5,19). It was obtained from the physical tests that Thickness (0,32 – 0,64) mm; well tanned; Tensile Strength resistence (106,07 – 109,73) kg/cm2; Flexibility (53,11 – 103,07) %; Slit Tear Resistance (13,48 – 39,22) kgf/cm; Stitch Tear Strength (74,51 – 137,79) kgf/cm, wet rub fastness tst shown a little discolourisation while dry rub fastness test shown no discolourisation.INTISARI Penelitian ini dimaksudkan untuk meningkatkan Mutu Kulit Sarung Tangan Golf Samak Krom, Produk dari industri penyamakan kulit di Indonesia. Menteri yang digunakan dalam penelitian ini adalah 32 sampel kulit sarung tangan golf samak krom. Analisa hasil uji dengan menggunakan Standar Deviasi dalam Des-criptive Statistic. Pengujian sampel dilakukan terhadap sifat-sifat organoleptis, kimiawi dan fisis dari kulit. Dari uji organoleptis diperoleh hasil uji cukup lemas, warnanya rata, nerf tidak lepas dan pegangannya mulur tetapi tidak elastis. Dari hasil uji kimiawi diperoleh hasil : nilai rentangan Kadar Air = (13,78 – 16,94) %; Kadar Cr2O3  =(1,43 – 4,91)%; dan pH = (3,78 – 5,30). Dalam uji fisis diperoleh hasil : nilai rentangan Tebal = (0,32 – 0,64) mm; Penyamakan = masak ; kekuatan Tarik = (106,07 – 199,73) kgf/cm2; Kemuluran Jahit = (74,51 – 137,79) kgf/cm serta kekuatan gosok cat basah = sedikit luntur dan kekuatan gosok cat kering = tidak luntur